Sodium anilinide–cyclohexylamide pair: synthesis, characterization, and hydrogen storage properties. Issue 13 (22nd January 2020) - Jing, Zijun; Yu, Yang; Chen, Ruting; Tan, Khai Chen; He, Teng; Wu, Anan; Pei, Qijun; Chua, Yong Shen; Zheng, Dewen; Zhang, Xi; Ge, Zhixin; Zhang, Fudong; et al.
Abstract : Metallo anilinide–cyclohexylamide pairs with promising thermodynamic properties for reversible hydrogen storage were successfully developed for the first time. Abstract : The lack of efficient hydrogen storage material is one of the bottlenecks for the large-scale implementation of hydrogen energy. Here, a series of new hydrogen storage materials, i.e., anilinide–cyclohexylamide pairs, are proposed via the metallation of an aniline–cyclohexylamine pair. DFT calculations show that the enthalpy change of hydrogen desorption (Δ H d ) can be significantly tuned from 60.0 kJ per mol-H2 for the pristine aniline–cyclohexylamine pair to 42.2 kJ per mol-H2 for sodium anilinide–cyclohexylamide and 38.7 kJ per mol-H2 for potassium anilinide–cyclohexylamide, where an interesting correlation between the electronegativity of the metal and the Δ H d was observed. Experimentally, the sodium anilinide–cyclohexylamide pair was successfully synthesised with a theoretical hydrogen capacity of 4.9 wt%, and the hydrogenation and dehydrogenation cycle can be achieved at a relatively low temperature of 150 °C in the presence of commercial catalysts, in clear contrast to the pristine aniline–cyclohexylamine pair which undergoes dehydrogenation at elevated temperatures.